2020
DOI: 10.2147/cmar.s259513
|View full text |Cite
|
Sign up to set email alerts
|

<p>The miRNA, miR-125b, Inhibited Invasion and Metastasis of Gastric-Cancer Cells by Triggering the STAT3 Signaling Pathway</p>

Abstract: Objective To investigate the function and the mechanism of miR-125b in the invasion and metastasis of gastric cancer and provide experimental basis for finding and developing new therapeutic strategies for gastric cancer. Methods The difference of miR-125b expression in gastric cancer tissues and adjacent tissues was detected by qRT-PCR. The same test was performed in different gastric cancer cell lines. The effect of miR-125b on SGC-7901 and BGC-823 gastric cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The same effect has been observed with Stt in BTIC glioblastoma cells ( 65 ); activation of STAT-3 induces upregulation of c-Myc, Cyclin D1 and Bcl-xL and protects against apoptosis to promote cell survival and proliferation ( 66 ). Other studies have shown that Stt and Napabucasin (a small molecule that targets STAT-3) decrease cell renewal potential and the number of colonies, thus preventing metastasis into bone tissue of PCa in a mouse model ( 67 ) also, Terphenylin suppress the tumor growth and metastasis in mouse model of gastric cancer ( 68 ) In addition, STAT-3 inhibition via galiellalactone decreases formation of metastatic, clonogenic and spherical stem PCa and gastric cancer cells ( 69 , 70 ). Androgen deprivation contributes to development of CRPC in patients ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…The same effect has been observed with Stt in BTIC glioblastoma cells ( 65 ); activation of STAT-3 induces upregulation of c-Myc, Cyclin D1 and Bcl-xL and protects against apoptosis to promote cell survival and proliferation ( 66 ). Other studies have shown that Stt and Napabucasin (a small molecule that targets STAT-3) decrease cell renewal potential and the number of colonies, thus preventing metastasis into bone tissue of PCa in a mouse model ( 67 ) also, Terphenylin suppress the tumor growth and metastasis in mouse model of gastric cancer ( 68 ) In addition, STAT-3 inhibition via galiellalactone decreases formation of metastatic, clonogenic and spherical stem PCa and gastric cancer cells ( 69 , 70 ). Androgen deprivation contributes to development of CRPC in patients ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…The tumorsuppressor activity of miR-125 was found to be mediated through its interaction with 3′UTR of STAT3 mRNA. 165 The above-indicated studies highlighted that the STAT3 pathway can be either modulated by miRNAs by directly interacting with STAT3 transcripts or by modulating the expression of endogenous inhibitors of STAT3 signaling such as SOCS3 to promote/regress GC progression.…”
Section: Gastric Cancermentioning
confidence: 99%